La participation communautaire pour définir la ville viable : questionnement sur l’appropriation de l’espace urbain - Éric Duchemin (VertigO)
The debate on sustainable urban development is actually at the connection of two movements.  It is now share by both local governments and citizens.  Structure for citizen participation in the life of their districts and/or wards, and to be actively involved in decision processes is a key for sustainable cities.  Furthermore, stakeholders should integrate common sense and uncertainties in decision processes to attain an urban sustainability.  Based on a field experiment we show that communication, animation abilities, as well as capacity to work in inter and transdisciplinary context, are required for professionals working in sustainable urban management.  Professional should also be able to include local knowledge in their practice and to be guides for citizens.